THE DEVELOPMENT OF LEARNING MEDIA BASED ON SAVI MODEL ON THE SCIENCE SUBJECT OF SECOND SEMESTER OF THE 3RD YEAR ELEMENTARY SCHOOL STUDENTS - I Gusti Made Adi Suryawan (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
The purposes of this research are (1) to develop and to implement the learning media based on SAVI model on the science subject of second semester of the 3rd year students elementary school of SD No. 3 Sukasada (2) to exactly know the response of the students of such kind of learning media.The type of research used is R&D (research and development) system withadapted development model from Dick and Carey, and also Alessi and Trollip. This research involved second semester of the 3rd year students of SD No. 3 Sukasada, especially for the science subject. The data were collected by interview and questionnaire. The result of the system were validated using questionnaire and then analyzed statistically using descriptive analysis.The results have shown that the average percentage of the individual test is97.7% and the average percentage of the group test is 93.9%, mean that the response of the students of the developed media is categorized as a very good result.